Nitrogen-doped carbon-based monatomic iron catalyst as well as preparation method and application thereof

By preparing nitrogen-doped carbon-based single-atom iron catalysts, the problems of high cost, high toxicity, and low utilization of active sites of Co-based catalysts were solved, achieving efficient activation of PMS to completely remove organic pollutants, which is suitable for industrial wastewater purification.

CN119524900APending Publication Date: 2025-02-28FOSHAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411598626.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing Co-based catalysts suffer from high cost, high biotoxicity, low utilization of active sites, and poor conductivity, resulting in low efficiency of PMS activation and degradation of organic pollutants, and difficulty in completely removing organic pollutants.

Method used

By preparing nitrogen-doped carbon-based single-atom iron catalysts, including calcining the metal framework material ZIF-8 at high temperature and mixing it with iron salts, ultrasonically dispersing it and calcining it again at high temperature, a nitrogen-doped carbon-based single-atom iron catalyst Fe-N/C is formed, which is used to activate permonosulfate (PMS) to generate active oxygen species.

Benefits of technology

It achieves complete removal of organic pollutants from wastewater within 1 minute, improves PMS activation efficiency, and has a degradation efficiency significantly higher than existing catalysts, making it suitable for industrial-scale production and advanced oxidation processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524900A_ABST
    Figure CN119524900A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wastewater purification, and particularly discloses a nitrogen-doped carbon-based monatomic iron catalyst and a preparation method and application thereof.The nitrogen-doped carbon-based material N-C is obtained by conducting simple high-temperature heat treatment on a metal framework structure material ZIF-8; fully adsorbing iron element on the surface of the N-C material by using an impregnation method to obtain an N-C / Fe composite precursor; and finally, carrying out heat treatment on the composite precursor to obtain the nitrogen-doped carbon-based monatomic iron catalyst Fe-N / C. The Fe-N / C catalyst prepared by the invention can thoroughly remove organic pollutants in wastewater by activating PMS within 1 minute, and the PMS activation efficiency of the Fe-N / C catalyst is remarkably improved compared with that of an existing iron-based catalyst, so that the Fe-N / C catalyst has a wide application prospect in a future advanced oxidation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater purification, in particular to a nitrogen-doped carbon-based single-atom iron catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of dye production and printing and dyeing industry, the discharge of dye-polluted wastewater, mainly anionic azo dyes, has increased dramatically. This type of pollution is highly persistent and difficult to biodegrade, posing a serious threat to human health and the ecological environment. Acid Orange 7 (AO7) is a typical anionic azo dye, which accounts for a large proportion of the current dye wastewater discharge. Advanced wastewater purification technology is urgently needed to completely degrade this type of pollutant. Advanced oxidation technology (AOPs) is an efficient, low-cost, environmentally friendly pollutant degradation technology, which is particularly effective in purifying organic polluted wastewater. The basic principle of AOPs is to activate permonosulfate (PMS) through a catalyst to produce a large number of highly oxidizing reactive oxygen species, such as sulfate radicals SO4 - ·, hydroxyl radical (·OH) or singlet oxygen ( 1 O2), etc. These active oxygen species can rapidly and non-selectively oxidize most of the organic pollutants in wastewater, thereby significantly improving the wastewater quality.

[0003] Chinese patent application number CN202210706537.4 discloses that transition metal cobalt (Co)-based catalysts exhibit good PMS activation and organic pollutant degradation performance, but Co-based catalysts also face the following four problems in the actual application process: First, the element cost of Co is relatively high, and the large-scale use of Co-based catalysts is not conducive to reducing the cost of wastewater treatment; second, the Co ions dissolved in wastewater are biologically toxic, and the use of Co-based compounds as PMS activation catalysts is likely to cause secondary pollution of water quality and increase the cost of wastewater treatment; third, the currently developed Co-based catalysts are mostly micron or nanoparticles in microscopic form, and the utilization rate of their active sites is low (the active sites inside the particles cannot be effectively utilized); fourth, most of the developed Co-based catalysts have poor conductivity, which is not conducive to the electron transfer process involved in the PMS activation or degradation process, thereby limiting the further improvement of the catalyst activity. In contrast, iron (Fe) is abundant in source, low in cost and low in biological toxicity, so the preparation of efficient and stable Fe-based catalysts for PMS activation and degradation of organic pollutants through microstructure design has important practical significance for promoting the commercial application of this technology.

[0004] Chinese patent application number CN202410017876.0 discloses the preparation and application of a ZIF-8-derived highly dispersed bimetallic Fe-Ni-NC material, the preparation method comprising: 1) preparing Fe-ZIF-8 first; 2) preparing Fe and Ni co-doped ZIF-8 by a dual solvent method; 3) preparing Fe-Ni-NC catalyst by pyrolysis. The PMS carbon-based single-atom catalyst prepared by this method can efficiently activate PMS, but it is difficult for the catalyst to completely remove organic pollutants by activating PMS, and it takes a long time (tens of minutes) to degrade organic pollutants.

[0005] Therefore, it is necessary to develop new nitrogen-doped carbon-based single-atom iron catalysts to efficiently activate PMS to degrade organic pollutants. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a nitrogen-doped carbon-based single-atom iron catalyst and a preparation method and application thereof.

[0007] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0008] One of the purposes of the present invention is to provide a method for preparing a nitrogen-doped carbon-based single-atom iron catalyst, comprising the following steps:

[0009] S1. The metal skeleton structure material ZIF-8 is ball-milled, and then calcined at 700-1100° C. for 1-3 h in a nitrogen atmosphere, and then naturally cooled to room temperature to obtain a nitrogen-doped carbon-based material NC;

[0010] S2, taking nitrogen-doped carbon-based material NC and iron salt with a mass ratio of 100:(1.47-6.17) and placing them in an excess solvent and mixing them thoroughly, and ultrasonically dispersing them for 5-60 minutes to allow the surface of the NC material to fully adsorb iron ions, and finally centrifuging and drying to obtain a NC / Fe composite precursor;

[0011] S3, NC / Fe composite precursor is placed in a nitrogen atmosphere and calcined at 700-1000°C for 1-3h, and then naturally cooled to room temperature to obtain a nitrogen-doped carbon-based single-atom iron catalyst Fe-N / C.

[0012] Furthermore, the preparation method of the metal skeleton structure material ZIF-8 in step S1 is:

[0013] 1) At room temperature, 2-methylimidazole and zinc oxide powders in a molar ratio of (1.6-2.8):1 are mixed evenly, loaded into an inner liner container of a reactor, filled with nitrogen atmosphere, and finally sealed;

[0014] 2) placing the sealed reactor in an explosion-proof oven, heating it to 160-240° C. and maintaining the constant temperature for solid phase reaction for 12-18 hours, and naturally cooling it to room temperature after the reaction is completed to obtain the metal skeleton structure material ZIF-8.

[0015] Preferably, in step S1, the ball-to-material ratio during ball milling is (20-60):1, the ball milling time is 6-12 hours, and the ball milling speed is 300-600 rpm.

[0016] Preferably, in step S2, the iron salt is ferric chloride.

[0017] Preferably, in step S3, the solvent is one of water, methanol, ethanol and isopropanol.

[0018] The second object of the present invention is to provide a nitrogen-doped carbon-based single-atom iron catalyst prepared by the above method.

[0019] The third object of the present invention is to provide a nitrogen-doped carbon-based single-atom iron catalyst for use in efficiently activating PMS to degrade organic pollutants.

[0020] Compared with the prior art, the present invention obtains nitrogen-doped carbon-based material NC by simply performing high-temperature (700-1100°C) heat treatment on metal skeleton structure material ZIF-8, and then uses impregnation method to make the surface of NC material fully adsorb iron element to obtain NC / Fe composite precursor, and finally heat treats the composite precursor (700-1000°C) to obtain nitrogen-doped carbon-based single-atom iron catalyst Fe-N / C; compared with the currently reported non-metallic or non-precious metal catalysts, the Fe-N / C catalyst prepared by the present invention has significant advantages in the efficiency of PMS activation and degradation of organic pollutants, and the preparation method of the catalyst is simple and easy to operate, and it is easy to achieve industrial-grade large-scale preparation; the Fe-N / C catalyst prepared by the present invention can completely remove organic pollutants (such as acid orange 7) in wastewater by activating PMS within 1 minute, and its PMS activation efficiency is significantly improved compared with the existing iron-based catalyst, so it has broad application prospects in future advanced oxidation processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Comparison of X-ray diffraction patterns of computer-simulated ZIF-8 crystals and the metal skeleton structure material ZIF-8 prepared in Examples 1 to 5.

[0022] Figure 2Characterization diagrams of different nitrogen-doped carbon-based single-atom iron catalysts: a is a comparison of the X-ray diffraction patterns of the Fe-N / C catalysts prepared in Example 3 and Example 5; b is the X-ray photoelectron spectrum (1s orbital) of the N element on the surface of the 2Fe-N / C-700 catalyst prepared in Example 3; c is a high-magnification HAADF-STEM image of the 2Fe-N / C-700 catalyst prepared in Example 3; d is the element (C, N, Fe) spectrum of the 2Fe-N / C-700 catalyst prepared in Example 3 under STEM mode.

[0023] Figure 3 The Mössbauer spectra test results of single-atom Fe on the surface of carbon-based single-atom iron catalysts doped with different nitrogen: a is the 2Fe-N / C-700 catalyst prepared in Example 3 57 Fe Mössbauer spectrum (test conditions: room temperature); b is the 2Fe-N / C-1000 catalyst prepared in Example 5 57 Fe Mössbauer spectrum (test conditions: room temperature).

[0024] Figure 4 The performance evaluation results of Fe-N / C catalyst prepared in each example for activating PMS to degrade Acid Orange 7 are shown.

[0025] Figure 5 These are the performance evaluation results of the Fe-N / C catalyst prepared in each example in activating PMS to degrade Acid Orange 7 under different initial pH conditions.

[0026] Figure 6 The performance evaluation results of 2Fe-N / C-700 catalyst, NC catalyst and pure carbon catalyst (KB-ECP) activated PMS to degrade Acid Orange 7 prepared in Example 3.

[0027] Figure 7 The performance evaluation results of the 2Fe-N / C-700 catalyst prepared in Example 3 for activating PMS to degrade Acid Orange 7 in different water quality environments (Qiandeng Lake ecological water, tap water, and ultrapure water).

[0028] Figure 8 for different anions (Cl - 、HCO3 - ) The performance evaluation results of the 2Fe-N / C-700 catalyst (Example 3) for activating PMS to degrade Acid Orange 7 were shown in Figure 3.

[0029] Fig. 9 The results are shown in the performance evaluation of different free radical scavengers (furfuryl alcohol FFA, tert-butyl alcohol TBA, methanol MeOH) on 2Fe-N / C-700 catalyst activated PMS for degradation of Acid Orange 7. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0031] Example 1. Preparation of 0.5Fe-N / C-700 catalyst

[0032] Take 821 mg of 2-methylimidazole and 370 mg of zinc oxide powder and mix them thoroughly. Place the mixed reaction raw materials in the inner tank of the reactor and fill it with nitrogen as a protective atmosphere, and finally seal it. Place the sealed reactor in an explosion-proof oven for solid-phase reaction at 200°C for 18 hours. After the reaction, the metal skeleton structure material ZIF-8 is obtained, which is ball-milled using a planetary high-energy ball mill. The ball milling jar has a rotation speed of 400 rpm, a ball milling time of 2 hours, and a ball-to-material ratio of 30:1. The above-mentioned ball-milled metal skeleton structure material ZIF-8 is placed in a tubular furnace for high-temperature heat treatment in a nitrogen atmosphere: the temperature is raised to 1100°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a nitrogen-doped carbon-based material (N / C-1100). 100 mg NC-1100 and 1.47 mg FeCl3 were placed in 10 mL isopropanol, ultrasonicated in a water bath for 60 minutes, then centrifuged and dried to obtain the NC-1100 / 0.5Fe composite precursor. Finally, the composite precursor was subjected to high temperature heat treatment in a nitrogen atmosphere: the temperature was raised to 700°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain the 0.5Fe-N / C-700 catalyst.

[0033] Example 2. Preparation of 1Fe-N / C-700 catalyst

[0034] Take 821 mg of 2-methylimidazole and 370 mg of zinc oxide powder and mix them thoroughly. Place the mixed reaction raw materials in the inner tank of the reactor and fill it with nitrogen as a protective atmosphere, and finally seal it. Place the sealed reactor in an explosion-proof oven for solid-phase reaction at 200°C for 18 hours. After the reaction, the metal skeleton structure material ZIF-8 is obtained, which is ball-milled using a planetary high-energy ball mill. The ball milling jar has a rotation speed of 400 rpm, a ball milling time of 2 hours, and a ball-to-material ratio of 30:1. The above-mentioned ball-milled metal skeleton structure material ZIF-8 is placed in a tubular furnace for high-temperature heat treatment in a nitrogen atmosphere: the temperature is raised to 1100°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a nitrogen-doped carbon-based material (N / C-1100). 100 mg NC-1100 and 2.99 mg FeCl3 were placed in 10 mL isopropanol, ultrasonicated in a water bath for 60 minutes, then centrifuged and dried to obtain the NC-1100 / 1Fe composite precursor. Finally, the composite precursor was subjected to high temperature heat treatment in a nitrogen atmosphere: the temperature was raised to 700°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain the 1Fe-N / C-700 catalyst.

[0035] Example 3. Preparation of 2Fe-N / C-700 catalyst

[0036] Take 821 mg of 2-methylimidazole and 370 mg of zinc oxide powder and mix them thoroughly. Place the mixed reaction raw materials in the inner tank of the reactor and fill it with nitrogen as a protective atmosphere, and finally seal it. Place the sealed reactor in an explosion-proof oven for solid-phase reaction at 200°C for 18 hours. After the reaction, the metal skeleton structure material ZIF-8 is obtained, which is ball-milled using a planetary high-energy ball mill. The ball milling jar has a rotation speed of 400 rpm, a ball milling time of 2 hours, and a ball-to-material ratio of 30:1. The above-mentioned ball-milled metal skeleton structure material ZIF-8 is placed in a tubular furnace for high-temperature heat treatment in a nitrogen atmosphere: the temperature is raised to 1100°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a nitrogen-doped carbon-based material (N / C-1100). 100 mg NC-1100 and 6.17 mg FeCl3 were placed in 10 mL isopropanol, ultrasonicated in a water bath for 60 minutes, then centrifuged and dried to obtain the NC-1100 / 2Fe composite precursor. Finally, the composite precursor was subjected to high temperature heat treatment in a nitrogen atmosphere: the temperature was raised to 700°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain the 2Fe-N / C-700 catalyst.

[0037] Example 4. Preparation of 2Fe-N / C-850 catalyst

[0038] Take 821 mg of 2-methylimidazole and 370 mg of zinc oxide powder and mix them thoroughly. Place the mixed reaction raw materials in the inner tank of the reactor and fill it with nitrogen as a protective atmosphere, and finally seal it. Place the sealed reactor in an explosion-proof oven for solid-phase reaction at 200°C for 18 hours. After the reaction, the metal skeleton structure material ZIF-8 is obtained, which is ball-milled using a planetary high-energy ball mill. The ball milling jar has a rotation speed of 400 rpm, a ball milling time of 2 hours, and a ball-to-material ratio of 30:1. The above-mentioned ball-milled metal skeleton structure material ZIF-8 is placed in a tubular furnace for high-temperature heat treatment in a nitrogen atmosphere: the temperature is raised to 1100°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a nitrogen-doped carbon-based material (N / C-1100). 100 mg NC-1100 and 6.17 mg FeCl3 were placed in 10 mL isopropanol, ultrasonicated in a water bath for 60 minutes, then centrifuged and dried to obtain the NC-1100 / 2Fe composite precursor. Finally, the composite precursor was subjected to high temperature heat treatment in a nitrogen atmosphere: the temperature was raised to 850°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain the 2Fe-N / C-850 catalyst.

[0039] Example 5. Preparation of 2Fe-N / C-1000 catalyst

[0040] Take 821 mg of 2-methylimidazole and 370 mg of zinc oxide powder and mix them thoroughly. Place the mixed reaction raw materials in the inner tank of the reactor and fill it with nitrogen as a protective atmosphere, and finally seal it. Place the sealed reactor in an explosion-proof oven for solid-phase reaction at 200°C for 18 hours. After the reaction, the metal skeleton structure material ZIF-8 is obtained, which is ball-milled using a planetary high-energy ball mill. The ball milling jar has a rotation speed of 400 rpm, a ball milling time of 2 hours, and a ball-to-material ratio of 30:1. The above-mentioned ball-milled metal skeleton structure material ZIF-8 is placed in a tubular furnace for high-temperature heat treatment in a nitrogen atmosphere: the temperature is raised to 1100°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain a nitrogen-doped carbon-based material (N / C-1100). 100 mg NC-1100 and 6.17 mg FeCl3 were placed in 10 mL isopropanol, ultrasonicated in a water bath for 60 minutes, then centrifuged and dried to obtain the NC-1100 / 2Fe composite precursor. Finally, the composite precursor was subjected to high temperature heat treatment in a nitrogen atmosphere: the temperature was raised to 1000°C at a rate of 10°C / min, maintained at this temperature for 1 hour, and then naturally cooled to room temperature to obtain the 2Fe-N / C-1000 catalyst.

[0041] The structures of the metal skeleton structure materials ZIF-8 prepared in Examples 1 to 5 were characterized respectively, and the analysis results are as follows: Figure 1 As shown. Figure 1 It can be seen that the metal framework structure material ZIF-8 prepared in each embodiment has exactly the same X-ray diffraction characteristics as the computer-simulated ZIF-8 crystal, indicating that the metal framework structure material ZIF-8 can be obtained by the solid phase reaction method described in each embodiment.

[0042] At the same time, the 2Fe-N / C-700 catalyst and the 2Fe-N / C-1000 catalyst prepared in Example 3 and Example 5 were characterized respectively. The analysis results are shown in the attached Figure 2 As shown. Figure 2 It can be seen that the X-ray diffraction spectra of (2Fe-N / C-700, 2Fe-N / C-1000) Figure 2 There is no diffraction signal of any Fe-based compound crystal material in a), indicating that the distribution of Fe in these catalysts is highly diffuse, and it is likely to form single-atom Fe active sites. X-ray photoelectron spectroscopy ( Figure 2 b) Characterization revealed that there was Fe-N on the catalyst surface. x Species. High magnification HAADF-STEM image of 2Fe-N / C-700 catalyst ( Figure 2 In c), it can be clearly seen that there is a single atom of Fe on the catalyst surface; further, the energy spectrum of different elements (C, N, Fe) on the catalyst surface is analyzed ( Figure 2 From the analysis in (d), we can see that the Fe element on the catalyst surface is evenly distributed, indicating that the single-atom Fe active sites are evenly distributed on the catalyst surface.

[0043] In order to further determine the coordination structure of single-atom Fe on the surface of the 2Fe-N / C-700 catalyst prepared in Example 3 and the 2Fe-N / C-1000 catalyst prepared in Example 5, Mössbauer spectroscopy test (room temperature condition) was performed on them. The test results are as follows: Figure 3 As shown, Figure 3 Figures a and b show that the single-atom Fe in the 2Fe-N / C-700 catalyst and the 2Fe-N / C-1000 catalyst has multiple coordination configurations, and the two main configurations are D1 (FeN4C12) and D2 (FeN4C10).

[0044] Application 1. Performance evaluation of nitrogen-doped carbon-based single-atom iron catalyst for activation of PMS to degrade acid orange 7 (AO7)

[0045] Acid Orange 7 (AO7) was used as a representative model pollutant. Multiple portions of simulated sewage with a concentration of 20 mg / L were prepared using Acid Orange 7 (AO7), and the PMS concentration in the simulated sewage was controlled to be 0.6 mM. Then, the catalysts prepared in Examples 1 to 5 were used to activate the Acid Orange 7 (AO7) in the PMS degradation reaction solution, respectively. The catalyst concentration was 100 mg / L, and the pH of the reaction solution was adjusted to be acidic. The reaction was carried out at 25° C. and the concentration of the model pollutant remaining in the solution after different reaction times was detected, which was recorded as C t , with time (min) as the horizontal axis, C t / C0 is used as the vertical coordinate to plot the degradation curves of the model pollutants in each system; at the same time, a control group experiment (Ketjen black KB-ECP, no catalyst condition) is designed to further evaluate the technical advancement of the catalyst of the present invention in PMS activation performance.

[0046] The performance evaluation results of Fe-N / C catalysts prepared in various examples for activating PMS to degrade Acid Orange 7 are shown in Figure 4 As shown, from Figure 4 It can be seen that the Fe-N / C single-atom iron catalysts prepared in all embodiments can completely remove AO7 in the reaction solution within 1 minute (removal rate 100%), showing extremely high degradation efficiency.

[0047] Furthermore, the pH of the reaction solution was adjusted to study the effect of the initial pH value of the reaction solution on the performance of the catalyst in degrading AO7. Figure 5 As shown by Figure 5 It can be seen that under the conditions of pH values ​​of 3, 4, 6.65, and 9.18, all 2Fe-N / C-700 catalysts can still completely remove AO7 from the reaction solution within 1 minute (removal rate 100%); under the condition of pH = 11.40, the 2Fe-N / C-700 catalyst can completely remove AO7 from the reaction solution within 5 minutes, which shows that the degradation efficiency of single-atom iron catalysts for AO7 will be weakened in a strong alkaline environment.

[0048] In order to highlight the technical advantages of the Fe-N / C single-atom iron catalyst prepared by the present invention in activating PMS to degrade organic pollutants, a pure carbon catalyst (KB-ECP) and a NC catalyst control group were designed. Example 3 Preparation of 2Fe-N / C-700 catalyst and NC catalyst and pure carbon catalyst (KB-ECP) for activating PMS to degrade acid orange 7 Figure 6 As shown by Figure 6 It can be seen that under the experimental conditions, the 2Fe-N / C-700 catalyst has a significantly superior degradation efficiency for AO7 compared to the control group catalyst, especially the KB-ECP catalyst can only remove about 50% of AO7 in the reaction solution after 30 minutes of reaction.

[0049] In order to further investigate the application potential of the catalyst of the present invention in sewage treatment technology, ultrapure water, tap water and Qiandeng Lake ecological water were used to prepare the initial AO7 reaction solution, and the influence of different water qualities on the catalytic performance of the 2Fe-N / C-700 catalyst prepared in Example 3 was studied. The performance evaluation results of the 2Fe-N / C-700 catalyst prepared in Example 3 in activating PMS to degrade Acid Orange 7 in different water quality environments (Qiandeng Lake ecological water, tap water, ultrapure water) are shown in the following figure: Figure 7 As shown, Figure 7 The results show that for AO7 solutions prepared from tap water and Foshan Qiandeng Lake ecological water, the 2Fe-N / C-700 catalyst can completely degrade AO7 within 5 minutes and 15 minutes respectively, with good results; but on the other hand, this degradation efficiency is weaker than that of AO7 solution prepared from ultrapure water, indicating that various impurities (especially other organic pollutants) in the water quality may affect the catalytic and degradation efficiency of the single-atom iron catalyst. Further quantitative studies on different anionic impurities (Cl - 、HCO3 - ) on the catalytic and degradation efficiency of 2Fe-N / C-700 catalyst. - 、HCO3 - The results of the performance evaluation of the 2Fe-N / C-700 catalyst (Example 3) for activating PMS to degrade Acid Orange 7 are shown in Figure 2. Figure 8 As shown by Figure 8 It can be seen that Cl - There is basically no negative impact on the degradation efficiency of 2Fe-N / C-700 catalyst, but HCO3 - To some extent, the degradation efficiency of the catalyst is reduced, which may be due to the HCO3 - The presence of changes the pH value of the reaction solution.

[0050] Finally, the activation mechanism of the catalyst of the present invention on PMS was studied by free radical scavenging experiments. It is known from the literature that furfuryl alcohol (FFA), tert-butyl alcohol (TBA), and methanol (MeOH) can quench singlet oxygen ( 1 O2), hydroxyl radical (·OH), ·OH and sulfate radical (SO4 - ·). The performance evaluation results of different free radical scavengers (furfuryl alcohol FFA, tert-butyl alcohol TBA, methanol MeOH) on the 2Fe-N / C-700 catalyst for activating PMS to degrade Acid Orange 7 are shown in Fig. 9 As shown by Fig. 9It can be seen that in the reaction solution containing FFA, the 2Fe-N / C-700 catalyst can hardly degrade AO7, but in the reaction solution containing TBA and MeOH, the 2Fe-N / C-700 catalyst still maintains the original degradation efficiency, that is, AO7 can be completely removed within 1 minute. The above results show that the main active oxygen species generated by the Fe-N / C single atom catalyst activating PMS are 1 O2, that is, the reaction system achieves the degradation of AO7 through a non-free radical pathway.

[0051] In summary, the nitrogen-doped carbon-based single-atom iron catalyst prepared by the present invention can efficiently activate PMS to degrade organic pollutants, and thus has broad application prospects in the field of wastewater purification technology.

[0052] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a nitrogen-doped carbon-based single-atom iron catalyst, characterized in that: The following steps are involved: S1. The metal skeleton structure material ZIF-8 is ball-milled, and then calcined at 700-1100° C. for 1-3 h in a nitrogen atmosphere, and then naturally cooled to room temperature to obtain a nitrogen-doped carbon-based material NC; S2, taking nitrogen-doped carbon-based material NC and iron salt with a mass ratio of 100:(1.47-6.17) and placing them in an excess solvent and mixing them thoroughly, and ultrasonically dispersing them for 5-60 minutes to allow the surface of the NC material to fully adsorb iron ions, and finally centrifuging and drying to obtain a NC / Fe composite precursor; S3, NC / Fe composite precursor is placed in a nitrogen atmosphere and calcined at 700-1000°C for 1-3h, and then naturally cooled to room temperature to obtain a nitrogen-doped carbon-based single-atom iron catalyst Fe-N / C.

2. The method for preparing the nitrogen-doped carbon-based single-atom iron catalyst according to claim 1, characterized in that: The preparation method of the metal skeleton structure material ZIF-8 in step S1 is: 1) At room temperature, 2-methylimidazole and zinc oxide powders in a molar ratio of (1.6-2.8):1 are mixed evenly, loaded into an inner liner container of a reactor, filled with nitrogen atmosphere, and finally sealed; 2) placing the sealed reactor in an explosion-proof oven, heating it to 160-240° C. and maintaining the constant temperature for solid phase reaction for 12-18 hours, and naturally cooling it to room temperature after the reaction is completed to obtain the metal skeleton structure material ZIF-8.

3. The method for preparing the nitrogen-doped carbon-based single-atom iron catalyst according to claim 1, characterized in that: In the step S1, the ball-to-material ratio during ball milling is (20-60):1, the ball milling time is 6-12 hours, and the ball milling speed is 300-600 rpm.

4. The method for preparing the nitrogen-doped carbon-based single-atom iron catalyst according to claim 1, characterized in that: In the step S2, the iron salt is ferric chloride.

5. The method for preparing the nitrogen-doped carbon-based single-atom iron catalyst according to claim 1, characterized in that: In step S3, the solvent is one of water, methanol, ethanol and isopropanol.

6. A nitrogen-doped carbon-based single-atom iron catalyst prepared by the method according to any one of claims 1 to 5.

7. Use of the nitrogen-doped carbon-based single-atom iron catalyst as claimed in claim 6 in efficiently activating PMS to degrade organic pollutants.

Citation Information

Patent Citations

  • Preparation method of cobalt oxide catalyst as well as product and application thereof

    CN114950435A

  • Preparation and application of ZIF-8 derived high-dispersion bimetallic Fe-Ni-N-C material

    CN118059910A